PENDUGAAN EROSI DAN PERENCANAAN KONSERVASI TANAH DAN AIR PADA DAERAH ALIRAN SUNGAI OTAN KABUPATEN TABANAN - KUSMAWATI, TATIEK (Agrotrop : Journal on Agriculture Science; Vol 1 No 1 (2011))
Erosion Prediction and Planning of Soil Water Conservation at Otan Watershed, Tabanan Regency The aims of this research was to predict the erosion and planning of soil and water conservation when the erosion is more than tolerable erosion. The USLE (Universal Soil Loss Equation) was used to predict erosion and planning of soil and water conservation. The result showed that the erosion level in this area was varied from very slight to very severe. The lowest erosion was on land unit 11 and 12 which were on the forest land. Slight erosion occurred on land units 2, 3, 4, 5, 10, 13, 18, 20, 22, 23, 25, 26, 28, 31, 32, 33, 34, 36, 37, 40, 41, and 43 on the use of forest land, irrigated fields, and mix crop land. Moderate erosion can be found at cocoa plantations, coffee plantations, scrub and dry land (land unit 1, 8, 16, 30, 38, dan 45). Severe and very severe erosion occurs at mixed crop land, coffee plantations, mixed crop and dry land (land unit 35 and 6, 7, 9, 14, 15, 17, 19, 21, 24, 27, 29, 39, 42, and 44 ). The planning of soil and water conservation was focused on the very severe erosion by doing for some plant growing storied canopies, very high density, and constructed terrace for land unit of 6, 7, 14, 15 ,19, 21, 27, and, 29. While at land unit, 9, 17, 24, and 35 was purposed mixed estate crop with high density, it was combinated with mulch of 1 ton/ha and in land unit 39 were for traditional terrace with gogo rice and corn plant in rotation plantation.
Keywords: prediction of erosion, planning of soil water conservation